Automatic Speed Detection and PWM Signal Generation for Application in Dual Fuel System - Lee Chua, King; Zarina Mohd Muji, Siti; Fawzi, Mas; Sari, Suhaila (International Journal of Engineering and Technology, 2018)
Dual fuel injection can be implemented in vehicle by changing engine injector or manipulating signal from vehicleâ€™s Electronic Control Unit (ECU). Changing engine injector is costly, thus this paper focuses study to discover possibility to manipulate ECU signal using microcontroller. The study desired to detect motor speed automatically, and then produce a new Pulse Width Modulation (PWM) signal to navigate fuel injector. The capture/compare/PWM (CCP) module of PIC18F4520 device is utilized to record timing of input signal, determine its correseponding speed, and generate PWM signal with the designated duty cycle. The predefined duty cycles for the PWM signal are 25%, 50%, and 75% in the system. The program is debugged using MPLAB software and verified with a test circuit operating at 10MHz frequency using specific engineering software. The experimental results demonstrated the program manifests a promising achievement to the expected theoretical results.Â